A formação de professores a distância e o acesso de crianças de seis anos à linguagem escrita através de projetos de letramento - Ranzani, Ariane (Universidade Federal de São Carlos, 2014)
This research aims to discuss how an e-learning course of continuing education for literacy teachers may contribute to the development of a literacy project with six-year-old children, enabling their access to writing so that it becomes an activity. Our theoretical framework is based on the concepts of activity and personal sense of the Activity Theory, developed by Leontiev (1978a, 1978b, 2006a, 2006b) from the socio-historical perspective and literacy projects of New Literacy Studies (KLEIMAN, 2000, 2001, 2005, 2006, 2007, 2008, 2009, 2010, 2012; MARTINS, 2007, 2008, 2009, 2012; OLIVEIRA, 2010a, 2010b; OLIVEIRA; SANTOS, 2012; TINOCO, 2008) . This study, which is based on the qualitativeinterpretative paradigm, investigates issues relating to the relevance of continuing education of literacy teachers in a virtual learning environment as a way of motivating the teachers participation and as a possibility of sharing thoughts on how (including practice and theory) and why develop educational activities, involving different discourse genres through literacy projects with six-year-old children of the first year of elementary school so that these activities make sense for all involved in this process. The results show the importance of interaction with the social and cultural environment and mediation, as a principle of organization of teacher s pedagogical activity, for the development of children in the learning process, in the use of written language. Thus, the literacy projects show another look at the pedagogical practice and teaching activities with written language, as they highlight the importance of teachers, of their knowledge (TARDIF, 2002), their mediation in organizing activities with written language, as well as allowing children to get into the activity, socially motivated, learning and using the writing language through different discursive genres.
Keywords: Linguística; Língua materna; Alfabetização; Projetos de letramento; Formação de professores; Ensino da linguagem escrita; Literacy projects; Teacher s continuing education; Writing language teaching; LINGUISTICA, LETRAS E ARTES::LINGUISTICA